THE INFLUENCE OF VALUE-BASED MARKETING IN GENERATION Z TOWARDS SUSTAINABLE CONSUMPTION FOR ENVIRONMENTALLY FRIENDLY PRODUCT OF PERTIWI - Nabiihah Salma, Elshanti
Plastic waste in Indonesia amounts to 66 million tons per year, making it a difficult challenge to manage. In terms of the amount of plastic waste currently being dumped into the South China Sea per person (0.52 kg/person/garbage), Indonesia is currently ranked second in the world. These problems can create regional and ecological environmental hazards. The current state of the Earth is the result of irresponsible production and consumption. Therefore, sustainable consumption models reduce the use of natural resources, toxic materials, gas emissions, and pollutants over the life cycle of a product or service to meet basic needs and improve quality of life. This is also in line with Goal 12 of the United Nations Sustainable Development Goals (SDGs), which is to “achieve sustainable consumption and production (SCP) patterns.” This requires attention to what, how, and how much we produce and consume in order to use the earth's resources wisely and conserve them for future generations. The factor that supports the shift in consumption patterns towards sustainable consumerism is the consumer behavior of Generation Z which is influenced by environmental and social factors. According to research, most Generation Z believe that social commitment is very important to them, and businesses that practice society's best needs and deliver them through their actions will be more trusted. These data indicate that Generation Z is already aware of value-based marketing in Indonesia, but there are no significant studies or that have focused on how Generation Z specifically benefits from sustainable consumption. Therefore, understanding the connection is very important. Unfortunately, Pertiwi is currently still having difficulties in determining a marketing strategy using the right value-based marketing. Therefore, this study undertakes consumer understanding by identifying the relationship between value-based marketing and sustainable consumption and the general motivational factors that support Generation Z to engage in sustainable consumption. Pertiwi is an Indonesian company that manufactures eco-friendly products, particularly single-use sanitary napkins made from possible natural resources. Pertiwi aspires to be a company that provides consumer goods that are environmentally friendly, can fulfill consumer desires, and increase awareness and understanding of responsible consumption and its impact on the environment. This research was conducted using qualitative methods through narrative research interviews with 6 female informants who at least had experience using environmentally friendly products in Bandung and analyzed using manual and selective coding methods. The results show that value-based marketing increases sustainable consumption, and there is an impact of value-based marketing on daily consumption. In addition, it is explained about the views of the informants regarding the increase in value based marketing. Researchers have evaluated that there are 3 reasons why value-based marketing has an impact on sustainable consumption in Generation Z, namely being right in responding to needs, getting validation to do it, and getting influence to do it. In addition, researchers also found general motivations for sustainable consumption. There are 3 things that need to be considered, namely product standards, motivation, and challenges. Find out what the root of the problem is by trying to look at it from a different perspective, to find the root of the problem. By figuring out what the root cause of the problem is, you can fix it right away and it might make a big difference. Where if the solution is found it will be a general motivation for generation Z to carry out sustainable consumption. These findings can help Pertiwi to develop a value-based marketing strategy that is carried out by Pertiwi itself. Keywords: Consumption, Marketing, Sustainable, Value